2015
DOI: 10.9745/ghsp-d-15-00170
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accessing Emergency Medical Services in Accra, Ghana: Development of a Survey Instrument and Initial Application in Ghana

Abstract: Most respondents thought the number of ambulances insufficient and said they would rather use a taxi—perceived to be faster—in a medical emergency. Nevertheless, people generally had favorable attitudes of existing public ambulance services, although few knew of the toll-free emergency number and many thought it appropriate to use ambulances to transport corpses. Targeted public education, along with improved capacity of ambulance agencies to handle increased caseload, could improve use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 19 publications
5
56
4
Order By: Relevance
“…that are known to make urban slum dwellers susceptible to dengue, leptospirosis, and other communicable diseases [82,83]. A key lesson from the Ebola outbreak [84] in 2014 was that quarantines, which were used as a response measure in Guinea, Liberia, and Sierra Leone, resulted in large waste disposal burdens that put an even greater strain on the health of residents of informal settlements. (8) Immediate plan for mobility and health care.…”
Section: Introductionmentioning
confidence: 99%
“…that are known to make urban slum dwellers susceptible to dengue, leptospirosis, and other communicable diseases [82,83]. A key lesson from the Ebola outbreak [84] in 2014 was that quarantines, which were used as a response measure in Guinea, Liberia, and Sierra Leone, resulted in large waste disposal burdens that put an even greater strain on the health of residents of informal settlements. (8) Immediate plan for mobility and health care.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that 81.9% of referred patients arrived by means of public transport. This has been corroborated by others [2,3,6,16,29,30]. Even when ambulances are utilized, delay is often encountered as patients may need wait for ambulances to arrive from other locations or are asked to provide funds to fuel the vehicle [2, 4-6, 24, 29].…”
Section: Discussionmentioning
confidence: 77%
“…Even when ambulances are utilized, delay is often encountered as patients may need wait for ambulances to arrive from other locations or are asked to provide funds to fuel the vehicle [2, 4-6, 24, 29]. Indeed, our results demonstrate that transport by ambulance was only marginally better than by taxi and interestingly, even the general public has the perception that taxis are a faster form of transport than are ambulances, which needs to be addressed [30]. The facilities most likely to refer are least likely to have transport mechanisms and proper means of communication with the receiving hospital [3,4,6].…”
Section: Discussionmentioning
confidence: 80%
“…The ability of the emergency medical service personnel to take patients' medical history medical history is due to medical-providers' lack of skill in taking medical history and their negligence in patients' conditions (8). The results of the research done by Arora et al in 2014 showed that in patients admitted to the emergency department poor communication between medical care providers and patients was among the preventable errors during medical examinations which seriously affected the quality of medical history (7).…”
Section: Original Articlementioning
confidence: 99%